Effects Of Connectivism Practices In Mobile Learning Environment On Yemeni Higher Education Students’ Cognitive Engagement, Self-Regulated Learning, And Performance - Al-Sumaty, Rami Muqbel Ahmed (2023)
This study tested a research model developed based on a literature review of connectivism principles for understanding the relationship between the connectivism practices (autonomy, diversity, openness, and interactivity) and the students’ performance through the mediation of social learning strategies represented by self-regulated learning, and cognitive engagement in the mobile learning environment. The sample involved 218 participants, full-time undergraduate students from a public university in Yemen. The finding revealed a positive relationship between the four connectivism practices, namely, autonomy, diversity, openness, and interactivity with the participants’ performance in a mobile learning environment. Similarly, significant relationships were found between three connectivism practices, i.e., autonomy, openness, and interactivity with the mediator’s constructs of cognitive engagement and self-regulated learning. However, no significant relationship was found between diversity and the two mediating constructs. Furthermore, cognitive engagement, and self-regulated learning were found to influence higher education students' performance in a connectivist mobile learning environment. Meanwhile, the result confirmed that the proposed model had a high predictive ability to measure the outputs of the connectivist mobile learning environment.